The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1007/s00508-005-0359-2
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic fever with renal syndrome in the Pomurje region of Slovenia – An 18-year survey

Abstract: HFRS is endemic in the north-eastern part of Slovenia; PUUV and DOBV infections coexist, with PUUV being the main causative agent of HFRS. Demographic, clinical and laboratory findings in our patients with HFRS caused by PUUV were mostly in accordance with those published previously, but the ratio of patients with sinus bradycardia, oliguric renal failure and mildly elevated CSF protein concentration was rather high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 20 publications
(46 reference statements)
9
20
0
Order By: Relevance
“…The most common clinical symptoms reported in our patients (fever, chills, malaise, headache, and back and abdominal pain) were similar to those previously reported in Slovenia, Germany, and Croatia [12,25,26]. However, there are some differences in the frequency of symptoms as well as in disease severity compared to previous Croatian outbreaks.…”
Section: Discussionsupporting
confidence: 86%
“…The most common clinical symptoms reported in our patients (fever, chills, malaise, headache, and back and abdominal pain) were similar to those previously reported in Slovenia, Germany, and Croatia [12,25,26]. However, there are some differences in the frequency of symptoms as well as in disease severity compared to previous Croatian outbreaks.…”
Section: Discussionsupporting
confidence: 86%
“…Also, DOBV seropositive patients in our study had more severe renal impairment compared with the PUUV and non-id hantavirus positive patients as witnessed by the diuresis, serum urea and creatinine values during the acute stage of the illness. Our results are in line with previous reports from B&H, Croatia and Slovenia that associated DOBV with severe form of HFRS (13,14,15,16,17).…”
Section: Discussionsupporting
confidence: 94%
“…Reports from Croatia and Slovenia where PUUV and DOBV also coexist suggested that DOBV-infected patients exhibited significant differences in illness severity (13,14,15,16). DOBV infected patients suffered more frequently from acute renal failure requiring dialysis treatment, shock, visual disturbances, and severe thrombocytopenia, hemorrhagic complications and disseminated intravascular coagulation than in patients with PUUV infection (17).…”
Section: Introductionmentioning
confidence: 99%
“…HTNV (4,000 focus-forming units [FFU] in MEM) was inoculated by intraperitoneal injection into adult mice. After viral challenge, the mice were observed, and body weights were measured at 0 (preinfection) and 7,14,21,28,33,35, and 42 days postinoculation (dpi). At these time points, some of the animals were euthanized, and sera were collected and stored at Ϫ30°C.…”
Section: Virusmentioning
confidence: 99%
“…On the other hand, neutrophilia has been documented in patients with hantavirus infection (26,(35)(36)(37). However, neutrophilia is far less common in viral infections than in bacterial infections (38,39).…”
mentioning
confidence: 99%